O Semi-presidencialismo e o controlo da constitucionalidade em São Tomé e Príncipe - Seibert, Gerhard (Africana Studia, 2020)
When Sao Tome e Principe became a multiparty democracy in 1990 it chose, in spite of the particularities of this small archipelago, a governing regime based on the semi-presidential Portuguese system. The consequent cohabitation between government and President with extra executive competences, led the way to a series of political conflicts between the governing organs and have affected negatively the development of the country, and, consequently, raised constitutional questions. In an empiric perspective of law in action this article deals with the functioning of the controversial semipresidential system and with the regulation of constitutionality, two important aspects of the young democracy of this small African country.